The Increasing Importance of the Strategic Direction of Management in International Companies - Stefan-Markus SCHOEFER (Communications of International Proceedings, 2021)
The process of developing strategies and their transfer into practical and suitable measures should ultimately serve to achieve the company's goals and ensure that the company meets the requirements of the stakeholders based on its own visions. Strategies are influenced by a multitude of factors, changes of direction and shifts in priority are the consequence of an adjustment to an agile economic environment. Strategies should be understandable and comprehensible for everyone in the company, because they explain why managers and employees have to carry out certain measures and actions.
Keywords: Adaptable strategy; responsive management; strategic thinking; agile international companies.